(untitled) (Journal of Enam Medical College, 2014)
Fasciolopsiasis is a disease caused by the largest food-borne intestinal trematode known as Fasciolopsis buski. Here we report a case of a 50-year-old female who presented with upper abdominal pain and vomiting for one month. She was previously diagnosed as a case of choledocholithiasis. Endoscopic retrograde cholangio-pancreatography (ERCP) revealed stones along with two leaf-shaped worms which were removed from the duodenum of the patient. The worms were identified as F. buski by its unique morphology. Awareness regarding this parasitic infestation, especially in the rural area, should gain attention while formulating strategies to prevent and manage such infestation. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19681 J Enam Med Col 2014; 4(2): 123-125